Bigfoot, the Loch Ness monster, and unexplained creatures - Bougie, Matt (Paranormal investigations., 2018)
Offers a brief history of cryptozoology, then profiles the legends of Bigfoot and the Loch New Monster. Includes images and illustrations, sidebars, a glossary, sources for further learning, and an index.